The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00780-018-0374-6
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic evolution equations in Banach spaces and applications to the Heath–Jarrow–Morton–Musiela equations

Abstract: In this paper we study the stochastic evolution equation (1.1) in martingale-type 2 Banach spaces (with the linear part of the drift being only a generator of a C 0 -semigroup). We prove the existence and the uniqueness of solutions to this equation. We apply the abstract results to the Heath-Jarrow-Morton-Musiela (HJMM) equation (6.3). In particular, we prove the existence and the uniqueness of solutions to the latter equation in the weighted Lebesgue and Sobolev spaces L p ν and W 1,p ν respectively. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 46 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Having shown that the Besov spaces of modelled distributions are UMD spaces and of M -type 2, gives us access to the solution theories of SPDEs in these Banach spaces, see e.g. [Brz95,Brz97,vNVW08,BK18], and, consequently, we obtain novel existence and uniqueness results for mild solutions of semilinear SPDEs in spaces of modelled distributions. In the following we briefly illustrate this for SPDEs with finite dimensional noise but we would like to emphasize that the theory of SPDEs in Banach spaces works, of course, also in the case of infinite dimensional noises, cf.…”
Section: Semilinear Spdes In Spaces Of Modelled Distributionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Having shown that the Besov spaces of modelled distributions are UMD spaces and of M -type 2, gives us access to the solution theories of SPDEs in these Banach spaces, see e.g. [Brz95,Brz97,vNVW08,BK18], and, consequently, we obtain novel existence and uniqueness results for mild solutions of semilinear SPDEs in spaces of modelled distributions. In the following we briefly illustrate this for SPDEs with finite dimensional noise but we would like to emphasize that the theory of SPDEs in Banach spaces works, of course, also in the case of infinite dimensional noises, cf.…”
Section: Semilinear Spdes In Spaces Of Modelled Distributionsmentioning
confidence: 91%
“…In the following we briefly illustrate this for SPDEs with finite dimensional noise but we would like to emphasize that the theory of SPDEs in Banach spaces works, of course, also in the case of infinite dimensional noises, cf. [vNVW08,BK18].…”
Section: Semilinear Spdes In Spaces Of Modelled Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For details on the financial background we refer to, e.g., [5,9,11,22,23]. There is a large literature on the well-posedness of (5.3) in the mild sense, also in the (more interesting) case where (σ k ), hence α 0 , depend explicitly on the unknown u, with different choices of state space as well as with more general noise (see, e.g., [1,3,9,14,17,28], [25, §20.3]). Here we limit ourselves to the case where (σ k ) are possibly random, but do not depend explicitly on u, and use as state space H(R + ), which we define as the space of locally integrable functions on R + such that f ′ ∈ L 2 (R + , e wx dx), endowed with the inner product…”
Section: Parabolic Approximation Of Musiela's Spdementioning
confidence: 99%
“…The authors in [BLSa10] studied invariant measures for SPDEs in M-type 2 Banach spaces, under Lipschitz and dissipativity conditions, driven by regular noise. Recently, their method was extended in [BK18] to an SPDE, arisen in stochastic finance, in a weighted L p -space. We note that the authors in [BR16] showed the strong Feller property and irreducibility of (P t ) t≥0 , and thus the uniqueness of the invariant measure, if it exists, for the stochastic heat equation with white noise on L p (0, 1) with p > 4.…”
Section: Introductionmentioning
confidence: 99%